Research progress on 40 Hz sensory stimulation for the treatment of Alzheimer’s disease - Tang, Bing; Tao, Ming (Frontiers in Aging Neuroscience, 2026)
Alzheimer’s disease (AD) is a prevalent neurodegenerative disorder characterized by β-amyloid (Aβ) deposition, tau protein hyperphosphorylation, and synaptic dysfunction. In recent years, 40 Hz sensory stimulation—including visual, auditory, and multimodal modalities—has emerged as a novel, non-invasive intervention demonstrating potential efficacy in both animal models and preliminary clinical studies. Preclinical evidence indicates that such stimulation can markedly reduce cerebral Aβ burden (by approximately 37%–53%), inhibit tau protein phosphorylation, enhance neuronal network synchrony and synaptic plasticity, and improve learning and memory performance. Limited human trials suggest that 40 Hz sensory stimulation is safe and well tolerated in patients with mild cognitive impairment (MCI) and early-stage AD, with a slowing trend in cognitive scale score decline following intervention. This review summarizes the mechanisms of action, experimental evidence from animal models, and advances in clinical application of 40 Hz sensory stimulation in AD prevention and treatment. It further explores the potential for multimodal combination therapies integrating sensory stimulation with cognitive training, pharmacological interventions, and lifestyle modifications, and addresses challenges such as optimal timing of intervention and the influence of ambient electromagnetic fields in real-world settings. Current evidence supports 40 Hz sensory stimulation as a feasible, multi-target, and safe adjunctive intervention; however, its efficacy and applicability must be verified through multicenter, randomized controlled trials with long-term follow-up.